Developing Green Waqf Model for Environmental Issues - Rusydiana, Aam Slamet; Sukmana, Raditya; Laila, Nisful (SMART Insight, 2023)
The discussion on strengthening environmental issues for sustainable development is summarized in SDGs goal fifteen. On the other hand, waqf is an Islamic social fund instrument that has a sustainable nature and has relevance to SDGs, so it has the potential to be developed in its role in maintaining a more sustainable environment. This research seeks to look at waqf models that are relevant to the SDGs by prioritizing waqf models that can be implemented in Indonesia in line with SDGs goal 15 from the Maqasid al-Shariah perspective. Furthermore, this research proposes a model for realizing the 15th SDG goal, namely the preservation of terrestrial ecosystems based on waqf through a modified Green Waqf scheme